Specification of rock abrasiveness for the purposes of tunnel driving using TBM - Miklúová Viera; Krajecová Otília; Laba Milan; Krepelka Frantiek (Acta Montanistica Slovaca, 2000)
This article analyses rock abrasiveness that causes attrition (wearing down) of the disintegration indentors. In the case of drilling machines equipped with disc chipper tools it is the attrition of the discs. The attrition of the discs results in the reduction of the drilling rate and the increase in the specific disintegration energy, thus directly affecting the total economic outcome of the mining site (tunnel).Abrasiveness of the rock is the rocks ability to wear down the working tool during the mutual interaction between the working indentor and the rock in the mechanic rock disintegration process. The disintegration indentor wears down during the interaction, that changes its geometric dimensions, causing the increase in the contact area between the tool and the surface of the rock. The changes in these dimensions consequently alter the rate of advance of the drilling machine and the specific disintegration energy.Abrasiveness is therefore an overall result of physical and mechanical characteristics of the rock during the interaction between the disintegration indentor and the rock. In the present time there is no method that would formulate the rocks abrasiveness at the hands of physical-mechanical characteristics of the rock. Because the interaction between the tool and the rock depends on the characteristics of the tool, abrasiveness is at present a relative quantity, dependent also on the quality of the disintegration indentors. With the progress in the quality of disintegration tools, the abrasiveness and the attrition of the tool during mechanic rock disintegration changes. From this standpoint it is, in the course of determining the rocks abrasiveness in the laboratory procedures, needed to eliminate the impact of the disintegration indentor characteristics. By choosing one disintegration indentor type with predetermined physical-mechanical characteristics for the laboratory measurements, we can obtain abrasiveness that characterizes the examined rock. The process of interaction between the indentor and the rock is also influenced by the environment where the interaction takes place. The effect of the environment is not negligible and therefore it is, in the laboratory conditions of determining the abrasiveness, always necessary to provide for the same environment and thus eliminate its influence on the overall measurement, especially in the case of comparing the abrasiveness of different rocks.We have determined the abrasiveness according to the ON 44 1121 (1982) on three types of rocks.